Antiseptic efficacy of two mouth rinses in the oral cavity to identify a suitable rinsing solution in radiation- or chemotherapy induced mucositis - Paula Zwicker; Marcus Freitag; Florian H. Heidel; Thomas Kocher; Axel Kramer (BMC, 2023)
Abstract Objectives Oral mucositis caused by intensive cancer chemotherapy or radiotherapy frequently results in pronounced damage of the oral mucosa leading to painful oral hygiene. To support oral care, antimicrobial effective mouth rinses may be used. Thus, the efficacy of a hypochlorite-based mouth rinse (Granudacyn®), assumed to be highly biocompatible because of the compounds being part of the natural pathogen defense, as possible antiseptic agent in case of oral mucositis was compared to that of an octenidine based antiseptic mouth rinse (Octenidol® md). Materials and methods The study was conducted as monocentric, controlled, randomized, blind cross over comparative study on 20 volunteers. As a proof of principle, we performed the study on orally healthy subjects and not cancer patients. The efficacy was determined as reduction of colony forming units (cfu) on buccal mucosa as well as in saliva. After mouth rinsing for 30 s, samples were taken after 1 min, 15 min, 30 and 60 min. The lg-reduction was calculated as difference between lg-values of cfu pre- and post-treatment. Results Both antiseptic mouth rinses induced a significant reduction of cfu on buccal mucosa and in saliva 1 min after mouth rinsing. The effect persisted up to 60 min. The octenidine based rinse was significantly superior to the hypochlorite-based rinse up to the last sample 60 min after rinsing. However, the known cytotoxicity of octenidine argues against its application. Conclusion Within the limits of this study, due to its antiseptic efficacy, the hypochlorite-based rinse Granudacyn® can be regarded appropriate to support the oral hygiene in patients with a sensitive oral mucosa during an aggressive cancer chemotherapy and radiation treatment in case of oral mucositis.